2009
DOI: 10.1016/j.ejcts.2008.09.046
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocyte growth factor: a new mesothelial targeted therapy to reduce postoperative pericardial adhesions☆

Abstract: The stimulation of pericardial cells with KGF reduced the intensity of postoperative adhesions and facilitated the re-operation. This study suggests that the mesothelial regeneration is the new horizon in anti-adhesion therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 23 publications
0
14
0
2
Order By: Relevance
“…KGF can prevent and repair epithelium injuries of the skin, cornea, bladder, lungs, intestines, and liver through multiple approaches and multiple levels [32]. Lopes et al [13] employed KGF to prevent swine pericardial adhesions in their study and suggested that the use of growth factors targeting mesothelial cell proliferation or regeneration can reduce the severity of adhesions. However, it has not been reported that KGF can prevent peritoneal adhesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…KGF can prevent and repair epithelium injuries of the skin, cornea, bladder, lungs, intestines, and liver through multiple approaches and multiple levels [32]. Lopes et al [13] employed KGF to prevent swine pericardial adhesions in their study and suggested that the use of growth factors targeting mesothelial cell proliferation or regeneration can reduce the severity of adhesions. However, it has not been reported that KGF can prevent peritoneal adhesions.…”
Section: Discussionmentioning
confidence: 99%
“…KGF has rarely been reported to prevent intra-abdominal adhesions by promoting mesothelial cell regeneration. KGF has been shown to improve mesothelial cell proliferation, which may enhance fibrinolytic activity to potentially suppress postoperative adhesions [13]. This study investigated whether the combined administration of KGF and sodium hyaluronate (HA) can prevent intra-abdominal adhesions in rats by promoting the orderly repair of the injured peritoneal mesothelial cell layer.…”
Section: Introductionmentioning
confidence: 99%
“…The prevention of postoperative adhesions to make sternal re-entry safer and to avoid its potentially associated lifethreatening complications has been a longstanding endeavor in cardiac surgery. The multiplicity of the proposed strategies, which range from the topical application of agents stimulating the pericardial fibrinolytic function by mesothelial cells 1 to the placement of resorbable 2 or nonresorbable 3 pericardial substitutes, clearly demonstrates that none of these strategies has proven convincing enough to gain wide clinical acceptance. On the basis of the study of Lassaletta, Chu, and Sellke, 4 it would seem that this list of compounds and devices can now be completed by.vodka.…”
mentioning
confidence: 99%
“…Inúmeros problemas médicos são relatados como consequência da existência e da severidade das aderências pós-cirúrgicas, as quais dificultam futuras abordagens e adicionam maior morbidade e mortalidade às reoperações (Garrett e Matthews, 1989;Seeger, Kaelin et al, 1997;Bennett, Melanson et al, 2003;Lopes, Dallan et al, 2009).…”
Section: Carboximetilquitosanaunclassified
“…Fonte: http://www.medicinageriatrica.com.br/tag/pericardio/ Vários métodos têm sido investigados para prevenir ou diminuir a gravidade das aderências pós-cirúrgicas (Smith, 1968;Gallo, Artinano et al, 1982;Milgalter, Uretzky et al, 1985;Vandersalm, Okike et al, 1986), mas apenas após a utilização dos polímeros sintéticos ou dos biopolímeros é que os resultados se tornaram mais consistentes e reprodutíveis (Duncan, Yaacobi et al, 1988;Seeger, Kaelin et al, 1997;Krause, Zazanis et al, 2001;Lopes, Dallan et al, 2009 (Liu, Huang et al, 2007), epicloridrina (Demarchi, Debrassi et al, 2014), Lu, Sheng et al, 2009;Reves, Bumgardner et al, 2013), e genipina (Reves, Bumgardner et al, 2013;Bao, Chen et al, 2014), com o objetivo de controlar as propriedades físico-químicas e criar uma rede polimérica estável. Entretanto, agentes de reticulação sintéticos são altamente citotóxicos, apresentando baixa biocompatibilidade (Speer, Chvapil et al, 1980).…”
Section: Carboximetilquitosanaunclassified